1996
DOI: 10.1144/gsl.sp.1996.001.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Insect origination and extinction in the Phanerozoic

Abstract: Insects (Superclass Hexapoda) are the most successful group of living terrestrial arthropods and the richness of their fossil record is only just beginning to be realized with the recent publication of two extensive databases. Hexapods first appeared in the Early Devonian, post-dating the Cambrian ‘explosion’ of marine arthropods by some 140 Ma. The earliest Hexapoda belong to primitively wingless taxa; however, these ‘Apterygota’ comprise less than 1% of all hexapod species. The appearance of winged insects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 9 publications
3
61
3
Order By: Relevance
“…These facts, long casually observed, have suggested that key evolutionary changes have been responsible for generating much of the richness in this very diverse group, and four such evolutionary innovations have held centre stage [18,19]: the insect bauplan [35], wings [36], wing folding [21] and complete metamorphosis [23]. Here, we have reported evidence that both fossil family rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These facts, long casually observed, have suggested that key evolutionary changes have been responsible for generating much of the richness in this very diverse group, and four such evolutionary innovations have held centre stage [18,19]: the insect bauplan [35], wings [36], wing folding [21] and complete metamorphosis [23]. Here, we have reported evidence that both fossil family rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 68%
“…Four progressive evolutionary steps have traditionally been recognized in the evolutionary history of the hexapods, based on the sequence in which they appear in the fossil record [18,19] and phylogenies (e.g. [20]) (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This continuity indicates a shift from earlier fluid feeding on pollination drops of gymnosperms to subsequent nee taring on angiosperms. These transfers probably represent opportunistic cladogenetic events in the plant and fly lineages, with an effect at higher taxonomic ranks, seen in family-level diversity data (Labandeira & Sepkoski, 1993;Jarzembowski & Ross, 1996). It is unknown why, for pollinators, only the Diptera escaped the extinction blitz.…”
Section: Pattern 2: Lateral Transfermentioning
confidence: 99%
“…Although the family-level analyses of fossil insect diversity by Labandeira and Sepkoski (1993) need to be updated, these and other analyses (Jarzembowski & Ross, 1996;Dmitriev & Ponomarenko, 2002) indicate that the plateau in the earlier semilogarithmic rise of family-level insect diversity may be real, attributable to a biological event that transformed plant species dominance from gymnosperm to angiosperm. An alternative explanation is that this plateau represents a lull in the recovery of insect taxa from earlier deposits with high numbers of insect species.…”
Section: The Impact Of Mid Mesozoic Pollination Data On Understandingmentioning
confidence: 99%
“…Despite their antiquity and their biodiversity peak during the Permian (Labandeira & Sepkoski, 1993;Jarzembowski & Ross, 1996) the Palaeozoic "polyneopterous" insects are rarely considered in phylogenetic analyses. Nevertheless, the usefulness of inclusion of fossil taxa in phylogenies is widely admitted (Smith, 1994).…”
Section: Introductionmentioning
confidence: 99%